1993
DOI: 10.1590/s0103-90161993000300015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do crescimento e da utilização de nutrientes pelo amendoim

Abstract: Avaliaram-se os padrões de crescimento e de absorção de macro e de micronutrientes de quatro cultivares de amendoim, sendo três de lançamento recente, IAC-Oirã, lAC-Poitara e IAC-Tupã, todos de porte ereto e um mais antigo, Penápolis, de hábito rasteiro. Os resultados obtidos mostraram que os cultivares recentes apresentaram o mesmo padrão de crescimento e de acúmulo dos nutrientes e o cultivar a rasteiro, de ciclo mais longo, apresentou um padrão ligeiramente diferente. Dentre os cultivares estudados, IAC-Tup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 3 publications
4
9
2
2
Order By: Relevance
“…Among the nutrient analysis showed that the similarities with respect to the amount between treatments (N), phosphorus (P), magnesium (Mg), sodium (Na), sulfur (S) and boron (B), which implies that treatments had no effect on the accumulation of these elements. According [17] the boron and magnesium are translocated into the seed medium peanut 31.4% and 33.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the nutrient analysis showed that the similarities with respect to the amount between treatments (N), phosphorus (P), magnesium (Mg), sodium (Na), sulfur (S) and boron (B), which implies that treatments had no effect on the accumulation of these elements. According [17] the boron and magnesium are translocated into the seed medium peanut 31.4% and 33.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluating the growth and utilization of nutrients by peanut [17] stated that the elements absorbed into higher and lower quantity, are iron and copper, respectively. The same authors explain that iron is a micronutrient bit translocated to the seed (average 4.5% of the total uptake), as copper and zinc translocate 50.7% and 60.2% respectively of the total absorbed into the seed.…”
Section: Resultsmentioning
confidence: 99%
“…Os valores acumulados no tratamento com o nutriente, em relação ao tratamento com a omissão de P, nas diferentes partes analisadas, foram de 70,8 e 11,7; 24,4 e 3,1; 95,3 e 15,6 mg de P por planta, respectivamente, (Tabela 3). Feitosa et al (1993) observaram o acúmulo total de fósforo em quatro variedades de amendoim e obtiveram valores variando de 10,0 a 14,5 kg ha -1 de P e concluíram que a época de maior absorção pela parte aérea coincidiu com aquela de maior produção da massa de matéria seca da parte aérea.…”
Section: 2 G Kg -1 Nas Raízes Respectivamente (Tabela 2)unclassified
“…E ainda a informação disponível sobre o efeito de deficiências minerais em amendoim (FEITOSA et al, 1993) foi obtida na década de 90, com variedade não utilizada em nossas condições atuais e, portanto, existe a necessidade de pesquisas com essa cultura devido ao surgimento de novos genótipos.…”
Section: Introductionunclassified
“…In the Brazilian state of São Paulo, sugarcane producers have adopted for decades the management of peanuts in intercropping with sugarcane in the off-season period, giving various benefits to the main crop, such as improving soil fertility, nematode control and aggregation of additional income from peanut crops (Melo Filho & Santos, 2010), increased productivity of stalks (Aleoni & Beauclair, 1995), decrease in the nematodes population occurring in sugarcane (Ambrosano et al, 2011), better soil conservation due to soil cover in the heavy rainfall season (Volk et al, 2004) and nutrient cycling (Feitosa et al, 1993).…”
Section: Introductionmentioning
confidence: 99%